La duplicación pronominal como mecanismo de subjetivización en español e italiano - Urbaniak, Ewa (Neophilologica, 2017)
The pronominal duplication constitutes one of the mechanisms that are characteristic of Romance languages. There are many theories that try to explain this phenomenon, some from the syntactic and the other ones from the pragmatic perspective. The aim of this article is to analyse the pronominal duplication in Spanish and Italian from the point of view of a theory of subjectification. In other words, the subjective notions in the duplicative constructions are examined.